FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR - Sherly Oktavia; Agustpaosa Nariman (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research aims to determine the effect of leverage, asset structure, firm size and liquidity on financial performance in manufacturing company listed on the Indonesia Stock Exchange in 2018 – 2020. The sample was selected by purposive sampling method and the valid data were 105 companies. The data processing technique uses multiple regression analysis assisted by Software Eviews version 11.0 and Microsoft Excel 2013. The results of this study indicate that leverage, asset structure and firm size have a significant and positive effect on financial performance. And liquidity has no effect on financial performance. The implication of this research is the need to maximize assets and capital as a business developer because total assets indicate the size of the company that can attract investors to increase the company's financial performance.